The Meaning of Denotation and the Meaning of Connotation in the Lyrics of the Song "Roman Picisan" by Dewa-19: Semantic Study - Dedy Irawan (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the denotative and connotative meanings contained in the lyrics of the song “Roman Picisan” by Dewa-19 through a semantic study focusing on the analysis of meaning in aesthetic and emotional contexts. This song was chosen because it is rich in poetic diction, metaphors, and imagery that depict the dynamics of love more deeply than its literal meaning. This study used a qualitative descriptive method with documentation techniques to collect data in the form of words, phrases, and clauses containing both denotative and connotative elements. The data were then analyzed by interpreting the basic meaning and additional meanings that emerge through the use of figurative language.The results show that connotative meanings dominate over denotative ones in the lyrics of “Roman Picisan.” The seemingly simple lyrics actually convey powerful emotional messages, such as depictions of sudden love, suppressed love, emotional closeness, and heartache, depicted through the metaphors of “arrow,” “fragrance,” and “slicing promises.” The use of imagery such as “night of a thousand stars” also reinforces the romantic atmosphere, influencing listeners’ perceptions. These findings confirm that song lyrics, as a form of musical literature, possess complex layers of meaning and can be scientifically analyzed to understand how language functions as a means of aesthetic expression. This research contributes to semantic learning by presenting concrete examples of the application of meaning theory to creative texts. Furthermore, the interpretation of connotative meaning demonstrates its dynamic nature and the ability to change according to each listener’s emotional experience.